2020
DOI: 10.1097/md.0000000000022204
|View full text |Cite
|
Sign up to set email alerts
|

Modified grade 4 osteotomy for the correction of post-traumatic thoracolumbar kyphosis

Abstract: Many surgical procedures have been developed for the treatment of post-traumatic thoracolumbar kyphosis. But there is a significant controversy over the ideal management. The aim of this study was to illustrate the technique of modified grade 4 osteotomy for the treatment of post-traumatic thoracolumbar kyphosis and to evaluate clinical and radiographic results of patients treated with this technique. From May 2013 to May 2018, 42 consecutive patients experiencing post-traumatic thoracolumbar kyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The osteotomy sites were usually chosen at the apex of the deformity, and posterior column osteotomy (PCO), pedicle subtraction osteotomy (PSO), modified grade 4 osteotomy, and vertebral column resection (VSR) were chosen depending on the severity and pattern of the curvature. 18 , 19 PCO includes Smith–Petersen osteotomy (SPO) and Ponte osteotomy. SPO involves resection of the lower facet joint and joint capsule.…”
Section: Methodsmentioning
confidence: 99%
“…The osteotomy sites were usually chosen at the apex of the deformity, and posterior column osteotomy (PCO), pedicle subtraction osteotomy (PSO), modified grade 4 osteotomy, and vertebral column resection (VSR) were chosen depending on the severity and pattern of the curvature. 18 , 19 PCO includes Smith–Petersen osteotomy (SPO) and Ponte osteotomy. SPO involves resection of the lower facet joint and joint capsule.…”
Section: Methodsmentioning
confidence: 99%
“…In recent 20 years, RPTK has achieved good clinical e cacy through PSO or modi ed PSO technology, [5][6][7][8][9][10][11][12][13] but there are some complications such as large amount of osteotomy, severe trauma, excessive blood loss, severe spinal cord shortening, and spinal cord injury. It has been reported that classical transpedicular osteotomy technique or modi ed pedicle osteotomy technique removes half of the pedicle and half of the vertebral body combined with the injured disc, which can lead to the intraoperative blood loss of up to 1500-2200 mL.…”
Section: Discusssionmentioning
confidence: 99%
“…It has been reported that classical transpedicular osteotomy technique or modi ed pedicle osteotomy technique removes half of the pedicle and half of the vertebral body combined with the injured disc, which can lead to the intraoperative blood loss of up to 1500-2200 mL. [5][6][7][8][9] Hua et al…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2015) reported similar techniques correcting kyphotic deformities , while the fulcrum of the osteotomy closure was modified more dorsally for a larger correction angle. Afterwards, many other scholars reported similar techniques via the trans-intervertebral approach, while there were nuances between each technique in osteotomy correction geometry ( Obeid et al., 2018 ; Liu et al., 2020 ). However, the terminology of these osteotomies was confusing and lies beyond the Schwab-SRS osteotomy classification.…”
Section: Introductionmentioning
confidence: 99%